„Beste Landpartie Allgemeinmedizin“ (BeLA): motivationale Faktoren für Medizinstudierende für eine ländliche Berufstätigkeit – eine qualitative Befragungsstudie - Schelter, Frederik; Werner, Felix; Roos, Marco (Zeitschrift für Allgemeinmedizin, 2023)
Background: General practitioner (GP) care close to home is endangered by various factors. In Bavaria, the Beste Landpartie Allgemeinmedizin (BeLA) program aims to motivate students to work as (GPs) in rural areas. This study investigates the motives driving students to apply for the BeLA program and explores whether overarching factors influencing medical work in rural areas can be identified and used for recruitment. Methods: Eighteen guided exploration interviews were conducted. From the individual motivations, positive expectations and a negative counter-image of medical work in the countryside were individually developed, and an ideal image (positive counter-horizon) of the assumed own medical professional activity in rural areas was drawn. Results: The aspects of country life mentioned by the students in the interviews can be divided into four categories: the quiet country life, the proximity to the patients, the family in the countryside, and the comparability with the city. The interviewees envision an ideal scenario of medical work in the countryside. The motivation is already so strong that the individual positive counter-horizon weakly weights negative aspects of the perfect image. The country is often idealized as a natural idyll. Conclusion: Upon entering the program, respondents strongly desire to become rural practitioners. To recruit undecided students considering rural practice, alternative strategies may be necessary for such programs. The strong personal connection shown by those motivated to work in rural areas provides potential avenues for adjusting medical study admission criteria, especially regarding the rural doctor quota.
CRIS-Team Scopus Importer:2023-09-01
Keywords: General practice; Qualitative social research; Rural areas; Shortage of general practitioners

Betreuungsrecht - Status quo nach der Gesetzesänderung 2023 - Werner, Felix; Unger, Constantin (MMW Fortschritte der Medizin, 2023)
CRIS-Team Scopus Importer:2023-10-13

Changes in T2 Relaxation Time Mapping of Intervertebral Discs Adjacent to Vertebrae after Kyphoplasty Correlate with the Physical Clinical Outcome of Patients - Wegener, Lisa; Werner, Felix; Kleyer, Arnd; Simon, David; Uder, Michael; Janka, Rolf Matthias; Trattnig, Siegfried; Welsch, Goetz H.; Pachowsky, Milena (Diagnostics, 2022)
(1) Background: To assess whether clinical outcomes correlate with tissue changes in the intervertebral discs (IVDs) after kyphoplasty as treatment for vertebral fractures, quantitative MRI was applied. (2) Methods: Quantitative T2 mapping acquired in a 3 T MRI scanner of the thoracolumbar spine was performed in 20 patients two years after kyphoplasty. The IVDs adjacent and nonadjacent to the treated vertebrae were divided into six regions of interest (ROI), which were further categorised into inner (ROI 2–5) and outer (ROI 1 and 6) parts of the IVDs, and the T2 values were analysed. T2 values of adjacent discs were correlated with the items of questionnaires evaluating the clinical outcome (i.e., 36-Item Short Form Survey). (3) Results: Lower T2 values in adjacent IVDs correlated with poorer physical outcome two years after kyphoplasty. The inner part of the IVDs adjacent to treated vertebrae showed statistically significant lower T2 values in segments L2/L3 and L3/L4 compared to nonadjacent ones. Patients with lower T2 values showed more pain and physical limitations in everyday life. (4) Conclusions: Quantitative T2 mapping can detect IVD degeneration in patients after kyphoplasty and correlates with the physical outcome. This technique could help to gain better insights into alterations in tissue composition following kyphoplasty and the consequences for the patients’ quality of life.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Clinical outcome; Intervertebral disc; Kyphoplasty; MRI; T2 mapping

Development and evaluation of an interprofessional teaching concept for modern wound management - Bergendahl, Lukas; Werner, Felix; Schmidt, Anita; Ronicke, Moritz; Renner, Regina; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Background and objectives: The aim of the present study was to establish and evaluate a new interprofessional teaching concept on the topic of wound management. Methods: After determining the status quo using a survey among medical students, we developed a new teaching concept that included a 150-minute course aimed at providing students with the opportunity to gain hands-on wound management skills. This interprofessional course was offered at the existing ‘SkillsLab’ teaching facility. The participants’ subjective level of knowledge was assessed by questionnaire before and after the course. Results: Our survey among 190 medical students showed them to be very interested in gaining practical experience in the field of wound management. To date, 120 participants (54.8 % medical students; 45.2 % nursing students) have attended this new interprofessional course, which has been equally well received by both medical and nursing students. For all specific topics (diagnosis, treatment, use of wound dressings, debridement), course participation was associated with a significant increase in knowledge. Conclusion: Given its relevance in clinical practice, it is important for medical students to learn about the various aspects associated with the care of patients with chronic wounds. By offering new teaching concepts, dermatology in particular is well suited to help students gain a better understanding of the challenges related to wound management and to improve their practical skills. Wound management is an ideal topic for interprofessional learning.
CRIS-Team Scopus Importer:2020-09-11

Entwicklung und Evaluation eines interprofessionellen Lehrkonzepts zum modernen Wundmanagement - Bergendahl, Lukas; Werner, Felix; Schmidt, Anita; Ronicke, Moritz; Renner, Regina; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-10-09

Forschung zur Kulturellen Bildung in Deutschland seit 1990 – Bestand und Perspektiven. Ein Projektbericht. - Jörissen, Benjamin; Liebau, Eckart; Lohwasser, Diana; Klepacki, Leopold; Werner, Felix; Wagner, Ernst; Hartmann, Sylke (Perspektiven der Forschung zur kulturellen Bildung., 2014)

Patient-reported reactogenicity and safety of COVID-19 vaccinations vs. comparator vaccinations: a comparative observational cohort study - Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastião, Maria; Hueber, Susann; Warkentin, Lisette (BMC Medicine, 2023)
Background: In the course of the SARS-CoV-2 pandemic, multiple vaccines were developed. Little was known about reactogenicity and safety in comparison to established vaccines, e.g. influenza, pneumococcus, or herpes zoster. Therefore, the present study aimed to compare self-reported side effects in persons vaccinated against SARS-CoV-2 with the incidence of side effects in persons receiving one of the established vaccines. Methods: A longitudinal observational study was conducted over a total of 124 days using web-based surveys. Persons receiving either a vaccination against SARS-CoV-2 or one of the established vaccines (comparator group) were included. In the first questionnaire (short-term survey), 2 weeks after vaccination, mainly local and systemic complaints were evaluated. The long-term survey (42 days after vaccination) and follow-up survey (124 weeks after vaccination) focused on medical consultations for any reason. Multivariate analyses were conducted to determine the influence of the vaccine type (SARS-CoV-2 vs. comparator) and demographic factors. Results: In total, data from 16,636 participants were included. Self-reported reactogenicity was lowest in the comparator group (53.2%) and highest in the ChAdOx1 group (85.3%). Local reactions were reported most frequently after mRNA-1273 (73.9%) and systemic reactions mainly after vector-based vaccines (79.8%). Almost all SARS-CoV-2 vaccines showed increased odds of reporting local or systemic reactions. Approximately equal proportions of participants reported medical consultations. None in the comparator group suspected a link to vaccination, while this was true for just over one in 10 in the mRNA-1273 group. The multivariate analysis showed that people with SARS-CoV-2 vaccination were not more likely to report medical consultations; patients who had received a regimen with at least one ChAdOx1 were even less likely to report medical consultations. Younger age, female gender and higher comorbidity were mostly associated with higher odds of medical consultations. Conclusion: The rate of adverse reactions after established vaccinations was roughly comparable to previous studies. Two weeks after vaccination, participants in the SARS-CoV-2 vaccination group reported more local and systemic local reactions than participants in the comparator group. In the further course, however, there were no higher odds of medical consultations in either of the two groups. Thus, altogether, we assume comparable safety. Trial registration: DRKS-ID DRKS00025881 and DRKS-ID DRKS00025373.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; SARS-CoV-2; Survey; Vaccine

Reactogenicity and safety of COVID-19 primary immunisation and booster vaccination regimens: a comparative observational cohort study - Warkentin, Lisette; Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastiao, Maria; Hueber, Susann (BMC Medicine, 2023)
Background: Since the beginning of the COVID-19 vaccination campaigns, recommendations regarding the vaccination have been very dynamic. Although the safety and efficacy of different vaccines have been analysed, data were scarce for vaccine regimens combining different vaccines. We therefore aimed to evaluate and compare the perceived reactogenicity and need for medical consultation after the most frequently applied homologous and heterologous COVID-19 vaccination regimens. Methods: In an observational cohort study, reactogenicity and safety were assessed within a maximum follow-up time of 124 days using web-based surveys. Reactogenicity was assessed for different vaccination regimens 2 weeks after a vaccination (short-term survey). The following surveys, long-term and follow-up surveys, focused on the utilisation of medical services, including those that were not suspected to be vaccine-related. Results: Data of 17,269 participants were analysed. The least local reactions were seen after a ChAdOx1 − ChAdOx1 regimen (32.6%, 95% CI [28.2, 37.2]) and the most after the first dose with mRNA-1273 (73.9%, 95% CI [70.5, 77.2]). Systemic reactions were least frequent in participants with a BNT162b2 booster after a homologous primary immunisation with ChAdOx1 (42.9%, 95% CI [32.1, 54.1]) and most frequent after a ChAdOx1 − mRNA-1273 (85.5%, 95% CI [82.9, 87.8]) and mRNA-1273/mRNA-1273 regimen (85.1%, 95% CI [83.2, 87.0]). In the short-term survey, the most common consequences were medication intake and sick leave (after local reactions 0% to 9.9%; after systemic reactions 4.5% to 37.9%). In the long-term and follow-up surveys, between 8.2 and 30.9% of participants reported consulting a doctor and between 0% and 5.4% seeking hospital care. The regression analyses 124 days after the first and after the third dose showed that the odds for reporting medical consultation were comparable between the vaccination regimens. Conclusions: Our analysis revealed differences in reactogenicity between the COVID-19 vaccines and vaccination regimens in Germany. The lowest reactogenicity as reported by participants was seen with BNT162b2, especially in homologous vaccination regimens. However, in all vaccination regimens reactogenicity rarely led to medical consultations. Small differences in seeking any medical consultation after 6 weeks diminished during the follow-up period. In the end, none of the vaccination regimens was associated with a higher risk for medical consultation. Trial registration: DRKS DRKS00025881 (https://drks.de/search/de/trial/DRKS00025373 ). Registered on 14 October 2021. DRKS DRKS00025373 (https://drks.de/search/de/trial/DRKS00025881 ). Registered on 21 May 2021. Registered retrospectively.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; Survey; Vaccines

“The measures taken by the government overburdened the daily practice” – insights of the PRICOV-19 study on German general practitioners in times of COVID-19 - Stark, Stefanie; Schaubroeck, Emmily; Kluge, Marie; Burggraf, Larissa; Roos, Marco; Borowski, Eve; Van Poel, Esther; Willems, Sara; Kühlein, Thomas; Hueber, Susann; Werner, Felix (BMC Primary Care, 2023)
Background: The international study PRICOV-19 aims to assess the impact of the COVID-19 pandemic on the organisation of primary health care. The German part focuses on German general practitioners during the second wave of the COVID-19 pandemic. This paper addresses the following research questions: (1) How were changes in tasks on primary care and patient treatment perceived by GPs?, (2) What was the role of GPs during the pandemic, and how was their wellbeing?, (3) How did GPs perceive health policy measures?, and, (4) What influenced the attitudes of GPs on health policy measures? Methods: This study pursues a multi-country cross-sectional design. Data collection took place throughout Germany from 01.02. to 28.02.2021 with a quantitative online questionnaire consisting of 53 items. The questionnaire was analysed through descriptive and inferential analyses using correlation and multiple regression models. Results: The response rate was 20.4% (n = 349). The respondents were mainly GPs (59.6%) in single practices (62.5%) with a mean work experience of 15 to 20 years. GPs experienced a change in their work and practice organisation (80.3%). They felt a high responsibility (70.6%) and found their work has become more meaningful to them (76%). They also saw a lack of political support (75.2%) and that the measures taken by the government overburdened the daily practice (66.4%). Not many GPs were at risk of being distressed (53.4%) but rated the health policies rather negatively (60%). The multiple regression showed, the more GPs were exposed to risk of distress, the worse they assessed the government's measures. Conclusion: GPs perceived their work as relevant and felt confident they could fulfil their tasks, but noticed that health policy initially hardly supported the outpatient sector. Health policies should increase their competence in relation to primary care, ensure its needs and consider an active inclusion of GPs in preparedness plans.
CRIS-Team Scopus Importer:2023-10-20
Keywords: COVID-19; General practitioners; Health policy; PRICOV-19; Primary health care; Quality of care; Wellbeing

“What else to say?”-Primary health care in times of COVID-19 from the perspective of German general practitioners: An exploratory analysis of the open text field in the PRICOV-19 study - Stark, Stefanie; Kluge, Marie; Schaubroeck, Emmily; Werner, Felix; van Poel, Esther; Willems, Sara; Roos, Marco; Kühlein, Thomas; Burggraf, Larissa (PLoS ONE, 2023)
Background The international collaboration study PRICOV-19 -Primary Health Care in times of COVID-19 aims to assess the impact of the COVID-19 pandemic on the organisation of primary health care. The German part focuses on the subjective perceptions of general practitioners on primary health care and the impact of political measures during the second wave of the COVID-19 pandemic. Within this survey, the “open text field” of the questionnaire was utilised remarkably frequently and extensively by the respondents. It became clear that the content that was named needed to be analysed in an exploratory manner. Accordingly, this paper addresses the following question: What preoccupies general practitioners in Germany during COVID-19 that we have not yet asked them enough? Methods The data collection took place throughout Germany from 01.02.2021 to 28.02.2021with a quantitative online questionnaire consisting of 53 items arranged across six topics as well as an “open text field” for further comments. The questionnaire's open text field was analysed following the premises of the qualitative content analysis. Results The topics discussed by the respondents were: insufficient support from health policies, not being prioritised and involved in the vaccination strategy, feeling insufficient prepared, that infrastructural changes and financial concerns threatened the practice, and perceiving the own role as important, as well as that health policies affected the wellbeing of the respondents. One of the main points was the way general practitioners were not sufficiently acknowledged for their contribution to ensuring high-quality care during the pandemic. Discussion German general practitioners perceived their work and role as highly relevant during the COVID-19 pandemic. In controversy with their perception, they described political conditions in which they were the ones who contributed significantly to the fight against the pandemic but were not given enough recognition.
CRIS-Team Scopus Importer:2023-03-31